Retrospective analysis of junior female handball players` priorities - Frolova, L. S.; Timofeev, A. A.; Petrenko, Y. A.; Atamas, O. A.; Grechukha, S. V.; Gun`ko, P. N.; Suprunovich, V. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2017)
Purpose: fulfillment of retrospective analysis of junior female handball players` tactic priorities. Material: in the research junior female handball players of 15-16 yrs age (n=60) participated. The researches were conducted in 2006, 2010 and 2016 on the base of sport schools and physical culture colleges of Ukraine. We used author`s programs «Balltest» and «Handball skills». Results: indicators of junior female handball players` abilities and tactical thinking effectiveness in different periods of the research were received. Correlations of these indicators with physical potentials and throw fitness point at tactical priorities of the players. Comparative characteristic showed that junior female handball players of 2016 year of the research had better abilities for solution of complex team tasks with low sensor indicators. We found handball players` preferences to defensive and attacking actions in central zone of site. Conclusions: by universal character of tactic priorities junior female handball players of 2016 year of the research yield to the players of 2006 and 2010 years of the research. Junior female handball players of 2016 year of the research prevail in successful mental solution of position defense tactic tasks, especially in readiness to act as supporters.